Service-learning as an Effective Pedagogical Approach for Communication Educators - Sara Chudnovsky Weintraub (Central States Communication Association, 2018)
Service-learning combines the learning goals of a course with service to the community. Through service-learning, students engage in action and reflect on their experiences in order to connect what they see and do in the community with what they are learning in their courses. Whether service-learning projects account for part of a course or an entire course is centered on service-learning, service-learning works because it connects theory with practice. Service-learning is an important pedagogy because it offers students a chance to do meaningful work that helps their community and teaches them the importance of civic engagement.